The Children’s and the Teacher’s Participation in the Constitution of Playing in School - Martins, Cristiane Amorim; Cruz, Silvia Helena Vieira (Paidéia (Ribeirão Preto), 2020)
Considering the relations between play and child development and the marginalization of play at school, evidenced in previous studies, this case study aimed to analyze children’s and teacher’s participation in the constitution of playing in a public nursery school in Fortaleza. The following procedures were adopted: observation of the class (composed of 24 low-income children) routine; semistructured interview; elaboration and explanation of drawings; story to be completed; and symbolic game, with analysis both of this game and of play experienced at school along with the children. Analysis of the data collected allowed concluding that the sort of play valued by the teacher is that which is planned and conducted by her aiming at learning and training skills. Free play, valued by children, is seen by her as “a mess.” The absence of critical reflection on the adult-centered posture of society, plus to the scarcity of knowledge of the relations between play and child development, compromise the quality of the teacher’s work.